Four-field symmetry breakings in twin-resonator photonic isomers - Ghosh, Alekhya; Hill, Lewis; Oppo, Gian Luca; Del'Haye, Pascal (Physical Review Research, 2023)
Symmetry and symmetry breaking of light states play an important role in photonic integrated circuits and have recently attracted lots of research interest that is relevant to the manipulation of light polarization, telecommunications, all optical computing, and more. We consider four-field symmetry breaking within two different configurations of photonic dimer systems, both comprised of two identical Kerr ring resonators. In each configuration we observe multiple degrees and levels of spontaneous symmetry breaking between circulating photon numbers and further, a wide range of oscillatory dynamics, such as chaos and multiple variations of periodic switching. These dynamics are of interest for optical data processing, optical memories, telecommunication systems, and integrated photonic sensors.
CRIS-Team Scopus Importer:2024-12-16